Amoxicillin as an Option in Congenital Syphilis Management: A Case Report - Ringoringo, Harapan Parlindungan; Tambunan, Katherine Richel; Ananda, Fajar Khalis; Nawati, Felynawati; Permana, Yanuar Nusca (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Congenital syphilis (CS) is the second leading cause of preventable stillbirth globally. This case report shows that CS baby can be managed by amoxicillin with good results. CASE PRESENTATION: A term female baby was born through section cesarean on suspicion of syphilis of a 29-year-old mother, G4P3A0, 39 weeks gestation with normal APGAR score, and birth weight was 2330 g, birth length was 46 cm, and head circumference 32 cm. There are no abnormalities on physical examination. The baby is active and clinically sound. In history taking, the mother was diagnosed with syphilis in the first trimester of pregnancy but did not want to be treated. After birth, maternal serology showed that Treponema pallidum is reactive. Maternal VDRL was reactive at 1:1, while TPHA was reactive at 1:2560. Baby laboratory results showed Hb 18.4 g/dL, leukocytes 33,480/μL, platelets 278,000/μL, and hematocrit 54.7%. A peripheral blood smear showed neutrophilia with hypersegmentation and monocytosis due to suspected chronic inflammation. Baby VDRL was reactive at 1:16, while TPHA was reactive at 1:1280. The diagnosis was congenital syphilis with low birth weight and small for gestational age. After one month of treatment with oral amoxicillin, baby VDRL was reactive at 1:2, while TPHA was reactive at 1:320. At 1½ months, the baby’s hemoglobin is 10.1 g/dL. X-rays for chest, abdomen, and skeletal were within normal limits. The baby was given oral amoxicillin 50 mg/kg/day for a total of 3 months. When the baby was 4 months old, her growth and development were good with the VDRL reactive 1:1 and the TPHA reactive 1:160. CONCLUSION: In the unavailability of benzathine penicillin, amoxicillin may be considered an option in CS management.